Kelayakan tepung darah dalam pembuatan pakan untuk pertumbuhan ikan nila, Oreochromis niloticus) - Takou, Putri D.; Mokolensang, Jeffrie F.; Pangkey, Hanneke; Lumenta, Cyska; Manoppo, Henky; Wantasen, Adnan S. (Universitas Sam Ratulangi, 2021)
The purpose of this study was to determine the feasibility of blood meal in various level inclusins inÂ promoting Â the growth rate and nutrient utilization of O. niloticus. Â The results showed that the absolute growth of tilapia in treatment 2 (with a combination of 20%) was higher than the other treatments. The daily growth rate of tilapia in treatment 2 (3.5% / day) was higher than other treatments. Likewise, with the feed change value, treatment 2 showed significantly different from other treatments. The combination of tuna fish meal waste and blood meal showed significantly different results from the results of statistical tests